Stable isotopes reveal groundwater to river connectivity in a mesoscale subtropical watershed - Santarosa, Lucas Vituri [UNESP] (2021)
The Corumbataí River basin (São Paulo, Brazil) has a critical situation regarding water availability due to the intensive use to support agriculture and urbanization, requiring scientific information to face water demand. The aim of this study is to present a hydrological characterization based on the analysis of seasonal isotope variations (rainfall, groundwater, and surface water) and hydrometric data. Results indicate that baseflow contribution varies from 50 % to 70 % of the total flow, and water isotopic composition denotes a seasonal regime marked by the mixing of surface and groundwater in the wet period and groundwater discharge during the dry season. The results presented indicated the strong seasonal connection between atmospheric inputs and water movement across the basin, which poses an urgent need to diversify monitoring methods and create feasible regional and political regulations to control the effects on basin water resilience in the face of climate change and growing demand.